EUROPEAN VECTOR OF ECONOMIC DEVELOPMENT AND MANAGEMENT OF TOURIST DESTINATIONS' COMPETITIVENESS IN DIGITAL ECONOMY - Inna Irtyshcheva; Iryna Nadtochii; Nazariy Popadynets; Nataliya Hryshyna; Ihor Sirenko (International Journal for Quality Research, 2022)
The tourism sector remains one of the domains with growth paces consistently higher than those of global economic development. Expansion of digital information and communication technologies is an essential foundation for securing the competitiveness of tourist destinations and innovative products. Their boost caused the reformatting of leading tourist destinations into the smart tourism regions in early 2016. The methodology of the research in the practical framework of the paper is based on the calculation of the Travel and Tourism Competitiveness Index of the World Economic Forum after 2014. The paper suggests the implementation of best global practices of the introduction of digital technologies directed at improving the competitiveness of tourist destinations. The authors emphasize that nowadays, the future of the tourism industry requires the creation of smart destinations and smart regions, which are almost absent in Ukraine today.